Quest for the type species of the genus Hepatozoon – phylogenetic position of hemogregarines of rats and consequences for taxonomy. Issue 6 (18th August 2021) - Hrazdilová, Kristýna; Červená, Barbora; Blanvillain, Caroline; Foronda, Pilar; Modrý, David
Abstract : The genus Hepatozoon is the most diversified and prevalent of all hemogregarine genera, which leads to a range of taxonomic challenges. Under-sampling and missing molecular data from rat-originating Hepatozoon muris, the type species of the genus Hepatozoon, complicated all efforts of systematic revision of individual subclades. To clarify the taxonomy of Hepatozoon at the genus level and to restrict the usage of this generic name to a particular clade of hemogregarines, we analysed 18S rDNA sequences of Hepatozoon from three species of rats from two isolated island populations. To assess the genetic variability, we analysed complete mitochondrial genome sequences of the two closely related isolates. Phylogenetic analyses revealed the position of both closely related Hepatozoon genotypes within the 18S rDNA clade including rodent/amphibian/reptile sequences, seriously challenging the validity of the previously proposed genus Bartazoon .